THE EFFECT OF DIFFERENT CONCENTRATION OF β-CYCLODEXTRIN AND GUM ARABIC ON THE MICROENCAPSULATED MORINGA SEED OIL BY USING THE SPRAY DRYING METHOD - AANISAH, NUUR; ISTIYAS, YAYUK; IBRAHIM, NURLINA; ZUBAIR, MUHAMMAD SULAIMAN; SULASTRI, EVI (International Journal of Applied Pharmaceutics, 2025)
Objective: The aim of this study was to determine the impact of various concentrations of β-cyclodextrin and gum arabic on the characteristics of Microencapsulated Moringa Seed Oil (MSO). Methods: The soxhlation method was used to extract MSO. The resulting MSO was microencapsulated employing a spray dryer. The variations in of β-cyclodextrin: Gum arabic concentrations were made to determine the coating material suitable for this formula. The characterization includes organoleptic tests, FTIR, encapsulation efficiency, morphology, particle size and moisture content of microencapsulated MSO. Results: The results obtained from the particle size for F1, F2, F3, F4, and F5 were 5.42; 4.29; 4.23; 4.34; 5.15 µm, respectively. Then the percentage of encapsulation efficiency obtained was 74.42±0.13; 78.81±0.12; 82.27±0.07; 93.94±0.09; 71.50±0.11, respectively. The IR spectra shows no chemical interactions that occurred in the formulation of microencapsulated MSO. Conclusion: In conclusion, microencapsulated MSO formulated with β-cyclodextrin (40% w/v) was recommended as the most optimal formula with a smaller particle size (4.34 µm) among others and exhibited the highest microencapsulation efficiency.